Challenges and new ways of teaching journalism in times of media convergence - Tárcia, Lorena; Marinho, Simão Pedro P. (Brazilian journalism research, 2008)
This research investigated the training of journalists facing the challenges brought about by digital technology and the Internet. The objective was to develop strategies to assist students to become pro-active and so demand of the institution an educative process that satisfies the new professional requirements generated by media convergence. The results point to the need for journalism education to act together with the students in the search for alternatives capable of accompanying the changes, while also taking into consideration the users´ interactive and participatory possibilities. Journalism degree courses are currently operating in a fragmented way, as consequence of the reality of the analogical media, and need to improve in order to train journalists capable of facing the new market realities, without losing the capacity for ethical reflection on their social responsibilities.